Exposure to ultraviolet radiation, perception and protective measures in residents of the city of Huaraz-Ancash - Castillo Picón, Heraclio Fernando (2024)
ABSTRACT This paper seeks to relate the level of perception and the use of protective measures by the population to bodily harm caused by the incidence of ultraviolet (UV) radiation. The research is relational in scope, cross-sectional in design and without manipulation of variables. As a procedure for collecting information, the survey was defined as a method, the interview as a technique and the questionnaire as an instrument; this tool was developed by the researcher and validated by experts. A population sample of 267 residents was used. The data collected was processed using the SPSS v. 25.0 program. The results allow us to assert the existence of a direct correlation between the perception of ultraviolet (UV) radiation and the measures adopted for their protection by the inhabitants of the city of Huaraz.